2016
DOI: 10.18632/oncotarget.9039
|View full text |Cite
|
Sign up to set email alerts
|

BIS-mediated STAT3 stabilization regulates glioblastoma stem cell-like phenotypes

Abstract: Glioblastoma stem cells (GSCs) are a subpopulation of highly tumorigenic and stem-like cells that are responsible for resistance to conventional therapy. Bcl-2-intreacting cell death suppressor (BIS; also known as BAG3) is an anti-apoptotic protein that is highly expressed in human cancers with various origins, including glioblastoma. In the present study, to investigate the role of BIS in GSC subpopulation, we examined the expression profile of BIS in A172 and U87-MG glioblastoma cell lines under specific in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 65 publications
3
25
0
Order By: Relevance
“…However, little is known regarding the role of BIS and HSF1 in GSC-like SPs. A previous study demonstrating that BIS was involved in regulation of the GSC-like phenotype via signal transducer and activator of transcription 3 (STAT3) stabilization prompted us to investigate whether BIS depletion might affect HSF1 in SP-forming conditions [16]. In the present study, we demonstrated that BIS depletion downregulated HSF1 protein levels and altered its subcellular localization.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, little is known regarding the role of BIS and HSF1 in GSC-like SPs. A previous study demonstrating that BIS was involved in regulation of the GSC-like phenotype via signal transducer and activator of transcription 3 (STAT3) stabilization prompted us to investigate whether BIS depletion might affect HSF1 in SP-forming conditions [16]. In the present study, we demonstrated that BIS depletion downregulated HSF1 protein levels and altered its subcellular localization.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies, as well as increasing evidence, support this postulation as BIS has been shown to regulate several proteins, including microtubule-associated protein 1 light chain 3β (MAP1LC3B) [32], STAT3 [16], and myosin heavy chain [33]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent report demonstrated that BIS is linked to glioblastoma stemness by stabilization of the signal transducer and activator of transcription 3 (STAT3) [33]. These findings provide reliable evidence that BIS is a potential target for therapy.…”
Section: Introductionmentioning
confidence: 86%
“…GSLC was the most vicious cell type in GBM cells, involving in treatment resistance and recurrence of GBMs [2,5]. In order to study the properties of GSLCs, we firstly enriched them from two GBM cell lines using serum-free medium supplemented with growth factors as the literature reported [29][30][31]. CD133 is still the most commonly used cell markers of glioma stem cells [6,32] despite some disputes [33].…”
Section: Discussionmentioning
confidence: 99%